Circular RNA HIPK3 mediates epithelial–mesenchymal transition of retinal pigment epithelial cells by sponging multiple microRNAs - Yalan Feng; Fan Yang; Jijia Zheng; Lijun Shi; Tianhua Xie; Yunzhi Lin; Qian Shi (Scientific Reports)
Abstract Epithelial–mesenchymal transition (EMT) of retinal pigment epithelial (RPE) cells plays key roles in the pathogenesis of multiple vitreoretinal diseases, leading to profound and permanent vision loss. Circular RNAs (circRNAs) are widespread and functional endogenous RNAs that could regulate gene expression in eukaryotes. The functions of circRNAs in mediating EMT has been reported in several diseases. In the current study, we investigated the role of circRNA HIPK3 (circHIPK3) in EMT process of RPE cells (RPE-EMT). circHIPK3 is one abundant circRNA generated from the second exon of HIPK3 mRNA. We found that circHIPK3 expression was significantly increased in TGF-β1-induced RPE-EMT model. Silencing of circHIPK3 attenuated TGF-β1-induced RPE-EMT process, whereas forced expression of circHIPK3 could trigger EMT in RPE cells. Mechanistically, circHIPK3 regulates RPE-EMT process via sponging multiple microRNAs (miRNAs). This study provides novel insights into the mechanism of RPE-EMT. Targeting circHIPK3 might serve as a therapeutic strategy in RPE-EMT associated vitreoretinal diseases.